2011
DOI: 10.1007/s10551-011-0991-x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior and the Public Service Ethos: Whither the Organization?

Abstract: Public services worldwide have been subject to externally imposed reforms utilizing tools such as financial incentives and performance targets. The adverse impact of such reforms on a public service ethos has been claimed, but rarely demonstrated. Individuals within organizations work beyond their formal contracts of employment, described as Organizational Citizenship Behavior (OCB), to further organizational interests. Given New Public Management reform and the subsequent contextual changes in the way in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 99 publications
(136 reference statements)
2
26
0
10
Order By: Relevance
“…The OCB, are not compulsory or describe clearly in job descriptions, they are also not rewarded nor punished [2]. Previous research has indicated that OCBs can influence organizational performance [3] & [4]. The benefits of the OCB in improving organizational performance also mention by Podsakoff et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…The OCB, are not compulsory or describe clearly in job descriptions, they are also not rewarded nor punished [2]. Previous research has indicated that OCBs can influence organizational performance [3] & [4]. The benefits of the OCB in improving organizational performance also mention by Podsakoff et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…acting 'in the interests of the common good') (p. 34). 128 In our study, public service ethos was manifested in the work motivation to 'make a difference to the patient':…”
Section: Valuesmentioning
confidence: 76%
“…Definisi OCB adalah an interest in work that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organization"(Organ 1988) dalam Rayner, et al (2012). OCB terdiri dari lima dimensi yaitu altruism, conscientiousness, courtesy, sportmanship, dan civic virtue.…”
Section: Kajian Teorimentioning
confidence: 99%
“…OCB diukur dengan 4 item dari dimensi arah langsung ke organisasi dan 4 dimensi arah langsung ke individu (William dan Anderson, 1991). Pengukuran ini konsisten dengan Chen dan Yang (2012), Rayner et al (2012).…”
Section: Perilaku Kerja (Organization Citizenship Behaviour) Organizunclassified